2021
DOI: 10.4103/aian.aian_874_20
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Awareness, and Attitude Towards Dementia Amongst Medical Undergraduate Students

Abstract: Background: Current undergraduate medical academic curriculum does not emphasize on evaluation and management of dementia. The knowledge and attitude of medical students towards patients with dementia in India has not been ascertained previously. Objective: We aimed to assess the knowledge and attitude of final year medical students about dementia and Alzheimer's disease. We also aimed to assess if a dedicated sensitization cum teaching session by a group of interns doc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Although individuals with higher education might have better comprehension skills for understanding complex health issues, our data suggest that education level does not directly impact AD awareness [ 46 ]. Similarly, our research revealed no notable link between marital status and levels of AD knowledge, consistent with previous studies [ 47 – 49 ]. In contrast, a study conducted in Northern Ireland found a significant association between marital status and AD knowledge levels, potentially influenced by the age demographics of the participants [ 36 ].…”
Section: Discussionsupporting
confidence: 93%
“…Although individuals with higher education might have better comprehension skills for understanding complex health issues, our data suggest that education level does not directly impact AD awareness [ 46 ]. Similarly, our research revealed no notable link between marital status and levels of AD knowledge, consistent with previous studies [ 47 – 49 ]. In contrast, a study conducted in Northern Ireland found a significant association between marital status and AD knowledge levels, potentially influenced by the age demographics of the participants [ 36 ].…”
Section: Discussionsupporting
confidence: 93%
“…Based on the results of the questionnaire and the relevant literature, 27,[31][32][33][34][35][36][37] a communication module will be designed to enhance dental students' attitudes towards people with dementia. The module's content will include an overview of dementia and its prevalence, its impact on dental care, common challenges in communication with dementia patients, effective communication strategies and the importance of empathy and person-centred care in managing patients with dementia.…”
Section: Discussionmentioning
confidence: 99%
“…However, this lack of awareness is not limited to general public. A study conducted in a medical college in the state of Gujarat reported that only 49% of undergraduate medical students were aware of dementia symptoms (Patel et al, 2021). This is more concerning as the mean age at presentation of dementia is also lower in the Indian context (Das et al, 2012) and young-onset dementia in particular is more likely to be associated with delays in diagnosis (Mukku et al, 2019) as also demonstrated in one vignette scenario (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Mr Gautam vignette (STRiDE India, 2022)) . Therefore, poor awareness among GPs further contributes to diagnostic delays as highlighted in several case vignettes; this can be attributed to the significant lack of emphasis of dementia in the undergraduate medical curriculum (Patel et al, 2021).…”
Section: [Insert Table 2 Here]mentioning
confidence: 99%